Integrated Green Supply Chain Model to Reduce Carbon Emission with Permissible Delay-in-Payment Consideration - Muhammad Faisal Ibrahim; Maulin Masyito Putri (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
In practice, the policy of delaying payment periods is prevalent between players in a supply chain system. Generally, payments are made at the end of the permitted period. Supply chain management is one of the keys to corporate sustainability that the activities impact the environment. This paper aims to develop an integrated green supply chain model with a permissible delay in payment consideration. In this research, the author develops a mathematical model to find the effect of delay in payment on emissions costs without ignoring the economic performance of a supply chain. The author develops four different scenario models. Furthermore, numerical experiments and sensitivity analysis tests were conducted. The study results show that delay in payment is integrated into the supply chain system, which has a positive impact on reducing supply chain emissions costs.